Effective thickness dependence on charge carrier transport in electrolyte-gated organic field-effect transistors - Luginieski, Marcos (2022)
Organic field-effect transistors (OFETs) began to be studied in the 1980s. Since then, several studies have focused on improving the performance of these organic devices, investigating transport properties of conjugated polymers, device geometry, materials, types of junctions, etc. So many efforts have been made due to the advantages that OFETs show in comparison to their inorganic counterparts as low manufacturing cost, mechanical flexibility and manufactured through solution processing. More recently, the class of electrolyte-based transistors draws a lot of attention due to the possibilities of applications such as biosensors, neuromorphic interfaces, integrated circuits, to cite a few. Electrolyte-based transistors are commonly based on the same OFET architecture but replace its dielectric gate layer with a dielectric gate with ionic species as, e.g., ionic liquids or ion gel solid films. Within electrolyte-based transistors types, it is possible to obtain two distinguished modes of operation, whose transconductance occurs due to: (i) the field-effect only, naming it as Electrolyte-gated FETs (EGOFETs) or (ii) electrochemical doping, when ions diffuse into the semiconductor and naming it as Organic Electrochemical Transistors (OECTs). While OECTs received their first theoretical modeling in 2007, EGOFETs are still commonly described from models developed for the organic field-effect transistor. The present work aims at the theoretical modeling of OFETs and EGOFETs through constant and non-constant field-effect mobility dependent on the effective thickness along the semiconductor/channel. Considering effects on the charge carriers transport due to the percolation paths and an exponential shallow trap distribution, it was demonstrated that the present model can be comparable to previously models established for OFETs with advantages of enriched information about the variation of the thickness of the accumulation layer along the channel and its dependence on field-effect mobility. When considering applying the present model to EGOFETs charge carrier transport that has a high capacitance of the electrolytes, the model proved to be more suitable for describing the behavior of transistors with an electrolyte gate operating by field effect. Beyond the common modes of operation regimes from transistors under field-effect transconductance the model was capable of describing some non-ideal ones. One of these non-ideal effects is a growth of the output current curve between the transition of accumulation to saturation regimes, what will be called as a protuberance. This protuberance has been reported experimentally for a long time, attributed to several phenomenological hypotheses. Suitable fits from the present model and experimental data were made, whose analysis attributes this phenomenon to a transition from 2D to 3D transport in EGOFETs. Another non-ideal phenomenon is the non-ohmic behavior in the accumulation region from the output current curve that was fitted with the present model, attributing it as being dependent on the energetic exponential shallow traps distribution. The two mentioned non-ideal behaviors have never been modeled before in the proposed EGOFETs-models literature. Furthermore, the great advantage of this model is its simplicity, facilitating the understanding of the phenomena and the easy adjustment of experimental data.